2018
DOI: 10.1093/jas/skx081
|View full text |Cite
|
Sign up to set email alerts
|

Rumen bacterial community structure impacts feed efficiency in beef cattle

Abstract: The importance of the rumen microbiota on nutrient cycling to the animal is well recognized; however, our understanding of the influence of the rumen microbiome composition on feed efficiency is limited. The rumen microbiomes of two large animal cohorts (125 heifers and 122 steers) were characterized to identify specific bacterial members (operational taxonomic units [OTUs]) associated with feed efficiency traits (ADFI, ADG, and G:F) in beef cattle. The heifer and steer cohorts were fed a forage-based diet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 54 publications
3
70
0
Order By: Relevance
“…Studying the rumen microbiome using "-omics" technologies Previous studies have used metagenomic and meta-transcriptomic approaches to quantify microbial content/abundance and microbial gene expression, respectively, and its potential link to feed efficiency in cattle (Shabat et al 2016;Li and Guan 2017;Paz et al 2018). Research investigating the rumen metagenome and its association with feed efficiency has revealed differential bacteria abundances across divergent rumen metabolic efficiencies by classifying specific bacteria using operational taxonomic units (OTU; Paz et al 2018), which measure various microbial species and their abundance. Specific OTU have been characterized in beef cattle across divergent feed efficiency groups and revealed that specific OTU abundance from bacterial families, including Prevotellaceae and Lachnospiraceae, were associated with feed efficiency in beef steers (Paz et al 2018).…”
Section: The Role Of Rumen Microbiome On Feed Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Studying the rumen microbiome using "-omics" technologies Previous studies have used metagenomic and meta-transcriptomic approaches to quantify microbial content/abundance and microbial gene expression, respectively, and its potential link to feed efficiency in cattle (Shabat et al 2016;Li and Guan 2017;Paz et al 2018). Research investigating the rumen metagenome and its association with feed efficiency has revealed differential bacteria abundances across divergent rumen metabolic efficiencies by classifying specific bacteria using operational taxonomic units (OTU; Paz et al 2018), which measure various microbial species and their abundance. Specific OTU have been characterized in beef cattle across divergent feed efficiency groups and revealed that specific OTU abundance from bacterial families, including Prevotellaceae and Lachnospiraceae, were associated with feed efficiency in beef steers (Paz et al 2018).…”
Section: The Role Of Rumen Microbiome On Feed Efficiencymentioning
confidence: 99%
“…Research investigating the rumen metagenome and its association with feed efficiency has revealed differential bacteria abundances across divergent rumen metabolic efficiencies by classifying specific bacteria using operational taxonomic units (OTU; Paz et al 2018), which measure various microbial species and their abundance. Specific OTU have been characterized in beef cattle across divergent feed efficiency groups and revealed that specific OTU abundance from bacterial families, including Prevotellaceae and Lachnospiraceae, were associated with feed efficiency in beef steers (Paz et al 2018). Feed efficiency and rumen microbiome have been previously associated (Hayes et al 2013;Sasson et al 2017;Paz et al 2018), revealing that models used to explain feed efficiency traits (e.g., DMI, average daily gain, and gain to feed ratio) explained up to 20% of the total variation in feed utilization when including OTU abundance parameters (Paz et al 2018).…”
Section: The Role Of Rumen Microbiome On Feed Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ruminococci are cellulolytic, and are known to produce acetate, formate and hydrogen; all important metabolites of ruminal metabolism [37]. Rather than large changes in bacterial populations, these finer shifts in organisms have also been identified in other research [38,39]. Organisms, including Succinivibrio spp., Eubacterium spp., and Robinsoniella spp.…”
Section: Ruminant Microbiomes and Feed Efficiencymentioning
confidence: 99%
“…GI tract microbial communities of ruminants perform important roles in host metabolism (i.e. cellulose degradation) [12] and are largely distinct from those found in monogastric species. Rumen microbial fermentation provides key metabolic products for the host animal such as short chain fatty acids (SCFA) and vitamins via the breakdown of cellulose, hemicellulose, pectin and other ingested feed [13, 14].…”
Section: Introductionmentioning
confidence: 99%